3(x-4)=2(x-7)

Simple and best practice solution for 3(x-4)=2(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)=2(x-7) equation:


Simplifying
3(x + -4) = 2(x + -7)

Reorder the terms:
3(-4 + x) = 2(x + -7)
(-4 * 3 + x * 3) = 2(x + -7)
(-12 + 3x) = 2(x + -7)

Reorder the terms:
-12 + 3x = 2(-7 + x)
-12 + 3x = (-7 * 2 + x * 2)
-12 + 3x = (-14 + 2x)

Solving
-12 + 3x = -14 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-12 + 3x + -2x = -14 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-12 + 1x = -14 + 2x + -2x

Combine like terms: 2x + -2x = 0
-12 + 1x = -14 + 0
-12 + 1x = -14

Add '12' to each side of the equation.
-12 + 12 + 1x = -14 + 12

Combine like terms: -12 + 12 = 0
0 + 1x = -14 + 12
1x = -14 + 12

Combine like terms: -14 + 12 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| 8x-3=7x+4 | | 4z/7-6=-3 | | 0.05(y-5)+0.10y=0.05y-0.20 | | 17w+27=129 | | -14z=6-12z | | 5y+15+4=38 | | -5x+20=x+8 | | (9x+20)+(2y+7x)=90 | | 19-1-17y=-20-15y | | 5y+15=34 | | 25x+7Y-7= | | 7x-9=2x+5 | | -4=-x+3 | | p=3+2p | | x/15-7=-2 | | -2n-23=4n+37 | | 3-5x-1/10=x-1/5-x-3/2 | | 1/3-1/8= | | X+8=-5x+20 | | t-5=-7+3t | | 20z-33=40 | | 4(2x+4)+2(3x-5)= | | 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 |

Equations solver categories